Ideology, resistance, and sociopolitical dynamics in Indonesia: media narratives and resistance discourses on the chairman of the corruption eradication commission’s corruption case - Qathrunnada, Zalfa; Nugroho, Catur; Yusanto, Freddy; Wulandari, Astri; Wulan, Roro Retno (Frontiers in Communication, 2025)
Indonesia’s Corruption Eradication Commission (KPK) is an anti-graft organization established in 2003 that plays a vital role in preventing and eradicating corrupt practices in Indonesia. Ironically, KPK Chairman 2019–2023, Firli Bahuri, was named a corruption suspect on November 22, 2023. The incident of naming the KPK Chairman as a suspect by the police caused conflict between KPK and the Police Department and attracted the media’s attention. This article aims to discover how DetikCom, Kompas.com, and Tempo.co, produce texts and discourses of resistance by the KPK Chairman against being named a suspect. Researchers also tried to uncover the ideology and interests of the media in the production of corruption discourse in Indonesia based on the external context of media and politics in Indonesia. The author used the text analysis method with Norman Fairclough’s Critical Discourse Analysis to analyze 18 media texts. The researcher found that the resistance discourse packaged by Detikcom online media tends to support the law enforcement narrative by providing more space for the Police Department to convey evidence and processes carried out. Kompas.com emphasizes that Firli has the right to file a pretrial and that the legal process must be respected, giving the impression that the media respects Firli’s legal rights. Tempo.co emphasized the case’s legal aspects and processes, including Firli Bahuri’s pretrial submission. At the sociocultural level, there is a relationship between corruption cases in Indonesia, government policies, and public responses to the conflict discourse over the KPK chairman.